Biological functions and theranostic potential of HMGB family members in human cancers. (November 2020) - Niu, Liaoran; Yang, Wanli; Duan, Lili; Wang, Xiaoqian; Li, Yiding; Xu, Chengchao; Liu, Chao; Zhang, Yujie; Zhou, Wei; Liu, Jinqiang; Zhao, Qingchuan; Han, Yu; et al.
The high mobility group box (HMGB) protein family consists of four members: HMGB1, 2, 3, and 4. They share similar amino acid sequences and identical functional regions, especially HMGB1, 2, and 3. The homology in structure may lead to similarity in function. In fact, though their targets may be different, they all possess the fundamental function of binding and distorting target DNAs. However, further research confirmed they are distributed differently in tissues and involved in various distinct physiological and pathological cellular processes, including cell proliferation, division, migration, and differentiation. Recently, the roles of HMGB family members in carcinogenesis has been widely investigated; however, systematic discussion on their functions and clinical values in malignant tumors is limited. In this review, we mainly review and summarize recent advances in knowledge of HMGB family members in terms of structure, distribution, biochemical cascades, and specific mechanisms regarding tumor progression. Importantly, the diagnostic, prognostic, and therapeutic value of these proteins in cancers is discussed. Finally, we envisage the orientation and challenges of this field in further studies.